EVALUASI PROGRAM STRATEGI MENGHADAPI UJIAN NASIONAL DI MTsN MODEL PADANG TAHUN 2008 - Miftahir Rizqa (Lembaga penelitian dan pengabdian kepada masyrakat, 2015)
This research, aimed at evaluating the implementation of strategic program in facing the national examination in MTsN model Padang. The subject of this research is the IX grade teachers and IX students. They are 36 teachers and students all together. Those teacher teach math, English, Indonesian, and science. Meanwhile, the samples from students were taken by using random sampling and 60 of the students was used as samples. Questionnaire, wawancara and documentation was used to collect the data and was analyzed by using descriptive statistics. The result of this research shows that (1) the teachers pedagogy knowledge was considered good. 58,33% of the teacher had a good pedagogy knowledge. (2) KKG program was considered as a very good program. 61,11% had a very good participation. (3) the teachers also gave an efficient material to the students and used efficiently. 47,22% of the teachers used the time efficiently. (4) the program ran well. 93,33% of the students said the advising was good. (5) it was indicated by the increasing of the students’ try out result. (6) the teacher who responsible for the program did their job well. 55,56% is very good